KONTRIBUSI LATIHAN KONTRAKSI-RELAKSASI (PNF) DAN WEIGHT TRAINING TERHADAP DAYA LEDAK TENDANGAN DEPAN PENCAK SILAT PADA MAHASISWA KELAS PENCAK SILAT LANJUTAN PKO FIK UNIMED. - Novita . (LPPM Universitas Negeri Medan, 2014)
The purpose of this study was to determine the contribution of the contraction-relaxation exercises (PNF) and weight training for explosive power front kick martial arts. This research was conducted at the Faculty of Sport Sciences, State University of Medan. The total population of 38 students. Sampling using purposive sampling technique in order to obtain the sample amounted to 12 people who are students who have passed the basic courses and enter the martial arts martial arts courses continued. This study uses some statistical procedures for testing the hypothesis that refers to the statistical methods that test for normality. The results of this study are contributing simultaneously from contraction-relaxation exercises (PNF) and weight training exercises for explosive power front kick in the martial arts martial arts class students continued State University of Medan. This shows that there is a significant contribution to the results of the exercise contraction-relaxation and weight training exercises were conducted for 6 weeks can improve explosive power leg muscle on the front kick martial arts.Keywords: Flexibility tests and explosive power student's performance.